mTOR Signaling in Aquaculture Animals: A Central Nutrient‐Sensing Hub Orchestrating Growth, Metabolism, Health and Quality - Yue Liu; Kangsen Mai; Wenbing Zhang (Reviews in Aquaculture, 2025)
Functioning as a master coordinator, the mechanistic target of rapamycin (mTOR) coordinates nutrient availability and energy status to fundamental biological processes including growth, metabolism, and physiological homeostasis through evolutionarily conserved mechanisms. The capacity of mTOR to assimilate nutritional and metabolic signals places it as a central focus in aquaculture nutrition research. This review systematically synthesizes current knowledge on the regulatory mechanisms mediated by the mTOR in various physiological processes of aquatic animal species, with particular emphasis on the mTOR networks regulated by diverse dietary nutrients. It provides a comprehensive summary of the regulation of various feed ingredients in growth performance, metabolic homeostasis, immune responses, product quality optimization, and health maintenance via mTOR. Moreover, this review analyzes interspecies variations and dietary adaptations across aquatic animals and outlines future research prospects focusing on the mTOR networks. It aims to establish a scientific framework for advancing precision nutrition research by integrating molecular regulatory insights with dietary nutrients, ultimately facilitating efficient and sustainable aquaculture.